2006
DOI: 10.1080/01443610600747454
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia in colposcopy clinics: to screen or not to screen?

Abstract: The objective of the study was to assess the prevalence of Chlamydia trachomatis in our colposcopy clinic. A total of 337 consecutive patients newly referred to the colposcopy clinic between May and November 2003 were screened for chlamydia trachomatis. All our patients were referred by their GPs and none of the patients had had a recent chlamydia test performed. Four patients screened positive, overall giving a prevalence of 1.2% [95% CI 0.04-2.36%]. Three of those with positive results were in the 21 - 30 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Condom use may contribute to regression of cervical dysplasia and HPV changes, 37 and has been shown to decrease male‐to‐female transmission of HPV 38 . Educating about and offering screening for sexually transmitted infections should be considered, particularly in high‐risk populations 21 . Women should be reminded to receive recommended follow‐up and to continue to receive cervical cancer screening.…”
Section: Risk Reduction and Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Condom use may contribute to regression of cervical dysplasia and HPV changes, 37 and has been shown to decrease male‐to‐female transmission of HPV 38 . Educating about and offering screening for sexually transmitted infections should be considered, particularly in high‐risk populations 21 . Women should be reminded to receive recommended follow‐up and to continue to receive cervical cancer screening.…”
Section: Risk Reduction and Counselingmentioning
confidence: 99%
“…Some colposcopists may repeat a Pap test during the examination; however, both retrospective and prospective studies have shown limited clinical utility in repeating either liquid‐based or conventional cytology at the time of colposcopy 18–20 . Screening for gonorrhea and chlamydia may be considered in high‐risk populations 21–23 …”
Section: Visualization With Colposcopymentioning
confidence: 99%
“…Matiluko et al found a prevalence of chlamydia of 1.2 per cent in a prospective evaluation of 337 patients referred to the colposcopy clinic with abnormal cytology 19. The prevalence of chlamydia was 2.2 per cent in women ≤30 years of age newly attending the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of chlamydia was 2.2 per cent in women ≤30 years of age newly attending the clinic. Chlamydia was screened for using ELISA in this survey and in the study of Matiluko et al ,19 which was in the same geographic location. While the survey does show the occurrence of chlamydial infection in association with symptomatic cervical ectropion, the suggestion that there is a higher prevalence of chlamydial infection in patients with symptomatic ectropion compared with other women attending the colposcopy unit is limited by the small sample size and the number of positive results, but has been demonstrated by others 20…”
Section: Discussionmentioning
confidence: 99%